Development and psychometric testing of a pediatric chronic graft-versus-host disease symptom scale: protocol for a two-phase, mixed methods study - Mitchell, Sandra A.; Hunter, Rachael; Fry, Abigail; Pavletic, Steven Z.; Widemann, Brigitte C.; Wiener, Lori (Frontiers in Psychology, 2024)
Background: Chronic graft-versus-host disease (cGVHD) is a debilitating late complication of hematopoietic stem cell transplantation. It is often accompanied by extensive symptom burden.No validated cGVHD patient-reported outcome (PRO) measure exists to evaluate cGVHD symptom bother in children and adolescents younger than 18 years. This paper presents the study protocol for a multi-center, two-phase protocol to develop a psychometrically valid pediatric cGVHD Symptom Scale (PCSS) and a companion caregiver-proxy measure to capture the symptom burden experienced by children with cGVHD. In the first phase of the study, our aim is to evaluate the comprehension, clarity and ease of response of the PCSS through cognitive interviewing and to iteratively refine the measure to optimize content validity. In the second phase of the study, we will quantitatively examine the measurement properties of the PCSS in children and their caregiver-proxies.Methods and analysis : Eligible participants are children/adolescents ages 5 to 17 with cGVHD who are receiving systemic immunosuppressive treatment or have recently tapered to discontinuation. In the first phase, we are enrolling 60 child and caregiver-proxy dyads in three child age strata (5-7 year old, 8-12 year old, 13-17 year old). Semi-scripted cognitive debriefing interviews are conducted to assess comprehension, clarity, and ease of response of each PCSS item with the child alone, and then jointly with the caregiver-proxy to explore discordant ratings. In phase two, an age-stratified cohort of 120 child-caregiver dyads will be enrolled to evaluate test-retest reliability, construct validity and responsiveness. Anchors for known-groups validity include the PedsQL module and clinical variables, including cGVHD clinician-rated severity scores. In participants ages 13-17, we will also compare responses on the PCSS with those from the Lee cGVHD Symptom Scale, to gauge the youngest age at which adolescent respondents can comprehend this adult measure.Discussion: This study will yield a well-validated, counterpart measure to the Lee cGVHD Symptom Scale for use in children with cGVHD and their caregiver-proxies. This new patientreported outcome measure can be integrated into clinical trials and care delivery for pediatric transplant survivors to improve the precision and accuracy with which their cGVHD symptom experience is captured.